nalysis and Apply Thai Khon Costume Pattern into High-End Fashion Design - Jia HU , Jirawat Vongphantuset (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Thai Khon is the Intangible culture heritage of Thailand, is a traditional court drama that has a significant impact on the history of Thai literature and art. Thai Khon is a performance and cultural art that has been passed down from Thailand since the Ayutthaya dynasty. It integrates culture, art, and ritual. Thai Khon is not only drama arts, It also shows traditional Thai customs and historical culture. All aspects of Thai culture are infiltrated in Thai Khon. It is full of Thai cultural contents and character, and it is demonstrating own unique style as well.The existing studies show that the design forms of the color and pattern of Thai Khon costume still uses the original design inspiration, traditional Thai patterns,and primary colors, such as red, green, yellow. If apply these colors and patterns into high-end fashion design makes the costumes very eye-catching. In this research, the researcher collected and analyzed patterns of Thai Khon costume, and did information analysis by qualitative research method. Analyzing the pattern and the culture of Thai Khon costume through taxonomies and classifications. The purposes of this research are: classify Thai Khon costume patterns, explain their cultural connotations and apply into fashion design. This study can help the audiences to understand the Thai Khon costume patterns and Thai .